Matematika Diskrit Teori Graf Pada LRT dalam Mengatasi Kemacetan : Studi Literatur - Katharina Stefania Ade Jaro; Khopipah Khopipah; Napis Napis (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Traffic congestion in Jakarta has become a serious problem, affecting various aspects of life, such as time efficiency, environmental quality, and economic productivity. As one solution to overcome this problem, the Jakarta government is developing a mass public transportation system, including the Light Rail Transit (LRT). The LRT is expected to reduce congestion by providing a more efficient and environmentally friendly transportation alternative. In the process of planning and optimizing the LRT system, discrete mathematics, particularly graph theory, plays a very important role. Graph theory is used to model the LRT station network and track, with vertices representing stations and edges representing connecting lines between stations. With this model, various analyses can be performed to optimize the LRT line, such as finding the shortest path between two stations or evaluating the connectivity between existing stations. The use of graph theory allows the identification of more efficient routes, resulting in faster travel and reduced passenger waiting times. In addition, graph theory also plays a role in optimizing the LRT route by minimizing the number of transfers between stations or avoiding passenger congestion at certain stations. With proper route and network optimization, the LRT can make a significant contribution to reducing traffic congestion in Jakarta. Furthermore, the development of an efficient public transportation system also supports improved air quality and reduces reliance on private vehicles. Overall, the application of graph theory in LRT system planning is a strategic step towards creating more efficient and sustainable transportation in large cities like Jakarta. Beyond route optimization, graph theory is also very useful in analyzing route capacity and passenger distribution along the LRT system.